Clearing the fog: Contributions to a broader understanding of generational differences in the workplace - Sousa, I.C.; Ramos, S.; Carvalho, H.; Standifer, R. (15th Workshop on Research Advances in Organizational Behavior and Human Resources Management, 2018)
The topic of generations has been receiving a growing interest from scholars and practitioners. However, despite the extensive empirical research on generational diversity, findings are still mixed and unclear. We proposed that these inconsistencies can be explained by two different phenomena: perceived generational differences and age. Drawing up from Social Identity Theory (Tajfel and Turner, 1986), we hypothesized that perceived generational differences in work values outnumber actual differences. We also proposed that age is a more appropriate construct to explain differences in work values, hypothesizing that there are more actual age-related differences in work values than actual generational differences. A sample of 705 workers rated the degree to which they personally valued 15 work values and then indicated value ratings for these items for each of the three generations. Our two hypotheses received empirical support. Implications for research and practice are discussed.